Taxes versus quotas for a stock pollutant - Michael Hoel; Larry S. Karp (Fondazione Eni Enrico Mattei (FEEM), 1998)
We compare the effects of taxes and quotas for an environmental problem in which the regulator and polluter have asymmetric information about abatement costs, and the environmental damage depends on the stock of pollution. We thus extend to a dynamic framework previous studies in which environmental damages depend on the flow of pollution. As with the static analysis, taxes are more likely to dominate quotas the greater is the curvature of the abatement cost function relative to the environmental damage function. However, in the dynamic model, an increase in the discount rate, the stock decay rate, or either the regulator's or the firms' ability to make adjustments, all increase the likelihood that taxes dominate quotas. An empirical illustration of these results suggests that taxes dominate quotas for the control of greenhouse gases.
Keywords: H21; Q28; 330; Pollution control; Asymmetric information; Taxes and quotas; Stochastic control; Ökosteuer; Immissionsschutz; Asymmetrische Information; Stochastischer Prozess; Theorie